2001
DOI: 10.1161/01.cir.103.7.919
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ramipril and Vitamin E on Atherosclerosis

Abstract: for the SECURE InvestigatorsBackground-Activation of the renin-angiotensin-aldosterone system and oxidative modification of LDL cholesterol play important roles in atherosclerosis. The Study to Evaluate Carotid Ultrasound changes in patients treated with Ramipril and vitamin E (SECURE), a substudy of the Heart Outcomes Prevention Evaluation (HOPE) trial, was a prospective, double-blind, 3ϫ2 factorial design trial that evaluated the effects of long-term treatment with the angiotensin-converting enzyme inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
160
1
9

Year Published

2002
2002
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 627 publications
(179 citation statements)
references
References 36 publications
(24 reference statements)
9
160
1
9
Order By: Relevance
“…There was no difference in atherosclerosis progression rates, as measured, between the vitamin E and the placebo-treated groups. 12 This finding is an important contrast to previous evidence suggesting that use of an antioxidant agent might be an effective means of reducing excessive LDL cholesterol oxidation. It is likely that vitamin E therapy is limited to scavenging lipid-soluble oxidants, whereas ACE inhibition blocks vascular superoxide production at its source.…”
Section: Evidence From Clinical Trialscontrasting
confidence: 59%
See 3 more Smart Citations
“…There was no difference in atherosclerosis progression rates, as measured, between the vitamin E and the placebo-treated groups. 12 This finding is an important contrast to previous evidence suggesting that use of an antioxidant agent might be an effective means of reducing excessive LDL cholesterol oxidation. It is likely that vitamin E therapy is limited to scavenging lipid-soluble oxidants, whereas ACE inhibition blocks vascular superoxide production at its source.…”
Section: Evidence From Clinical Trialscontrasting
confidence: 59%
“…10,11 In the Study to Evaluate Carotid Ultrasound changes in patients treated with Ramipril and vitamin E (SECURE), a HOPE substudy, ACE inhibition, but not treatment with the antioxidant vitamin E, prevented the progression of atherosclerosis, as measured by the intimal-to-medial ratio of the carotid artery. 12 This is an important contrast to previous findings that suggested that use of an antioxidant vitamin might mitigate atherosclerosis by reducing excessive low-density lipoprotein (LDL) cholesterol oxidation. A brief overview of the role of ACE inhibitors and ARBs in lessening oxidative stress in the vascular system follows.…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…12 Among the 3,577 subjects with diabetes, those treated with ramipril (compared with placebo) for 4.5 years had a lower risk of death by 24%, myocardial infarction by 22%, and stroke by 33%. In the Study to Evaluate Carotid Ultrasound Changes in Patients Treated with Ramipril and Vitamin E (SECURE), 13 a HOPE substudy, ramipril led to dose-dependent decreases in carotid artery atherosclerosis progression as measured by B-mode ultrasonography. The Losartan Intervention For Endpoint reduction in hypertension study (LIFE) demonstrated superior effectiveness of the angiotensin receptor blocker (ARB) losartan over the beta blocker atenolol with regard to cardiovascular outcomes 14 in the subgroup of patients with diabetes, hypertension, and left ventricular hypertrophy.…”
Section: Blood Pressure Managementmentioning
confidence: 99%